A Critical Discourse Analysis of Trump-Biden’s First Presidential Debate - Khudhair Ashammari, Zina Abdul-Hussein (Eximia, 2021)
This study attempts to investigate two contrastive ideologies showed by Trump and Biden. In its widest sense, ideology represents a set of ideas and beliefs that an individual has and affects others. Such ideas and beliefs pave the way to the emergence of the field of Critical Discourse analysis(CDA henceforth). CDA originates from a socio-political ideologies and it endeavors to investigate language in its real use.